2021
DOI: 10.1016/j.jbc.2021.101255
|View full text |Cite
|
Sign up to set email alerts
|

Branched-chain amino acid metabolism controls membrane phospholipid structure in Staphylococcus aureus

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 56 publications
2
39
0
Order By: Relevance
“…The reactions were performed with nonradioactive substrates, the samples were acid precipitated, and the pellets hydrolyzed with Asp-N protease. This process liberates a tripeptide harboring the prosthetic group and attached acyl chains that were then separated and detected by LC-MS/MS ( 17 , 18 , 19 ). Acetyl-ACP was not detected in assays without MadA and was robustly detected in assays containing MadA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reactions were performed with nonradioactive substrates, the samples were acid precipitated, and the pellets hydrolyzed with Asp-N protease. This process liberates a tripeptide harboring the prosthetic group and attached acyl chains that were then separated and detected by LC-MS/MS ( 17 , 18 , 19 ). Acetyl-ACP was not detected in assays without MadA and was robustly detected in assays containing MadA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cultures were incubated at 37 °C until they reached an A 600 = 0.6. The extraction method, liquid chromatography column and gradient, mass spectrometry parameters, and the Q1 and Q3 masses for the acyl-CoA were exactly as described ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Metabolomics results also revealed some enriched pathways in glucose and carbon metabolism, such as C5-branched dibasic acid metabolism. Previous studies suggested that multiple factors in amino acid metabolism moonlight as regulators in the expressions of genes regulating bacterial virulence ( Lomas-Lopez et al, 2007 ; Frank et al, 2021 ). Our findings also showed that amino acid metabolism was significantly enriched according to KEGG analysis of metabolome and transcriptome data.…”
Section: Discussionmentioning
confidence: 99%